Living with nature and things: contributions to a new social history of the middle Islamic periods - Walker, Bethany J.; Al Ghouz, Abdelkader (Mamluk studies, 2020)
Angaben zur beteiligten Person Walker: Prof Dr Bethany J. Walker is Research Professor of Mamluk Studies at the University of Bonn and Director of the Research Unit of Islamic Archaeology. A historically-trained archaeologist, she directs several field projects in Jordan and Israel.